Assessment of Prescription Pattern of Systemic Steroidal Drugs in the Outpatient Department of Menelik II Referral Hospital, Addis Ababa, Ethiopia, 2019 - Wondmkun, Yohannes Tsegyie (Patient Prefer Adherence, 2021)
BACKGROUND: Because systemic corticosteroids are associated with severe adverse effects, a study on the prescribing pattern for rationalizing drug therapy is needed. OBJECTIVE: The purpose of this study was to assess the prescription pattern of systemic steroidal drugs at the outpatient department of Menelik II Referral Hospital, Addis Ababa, Ethiopia, 2019. METHODS: A cross-sectional study design was used to assess the prescription pattern of systemic steroidal drugs in the outpatient department of Menelik II Referral Hospital. A total of 384 patient charts were included in the study. The sample was selected by using a non-probability quota sampling method. The data was collected from patient charts by using a checklist and analyzed by using SPSS version 20 computer software package. Finally, the data was presented with tables, graphs and charts. RESULTS: A total of 384 patient medical charts were reviewed during the study period. From which, 61.2% were females and 22.4% were in the age group of 31–40 years. The majority, 63.5%, of systemic corticosteroid use was indicated for respiratory disorders and the most frequently prescribed drug was prednisolone (42.4%). It was also found that intermediate acting corticosteroids (prednisolone and methyl prednisolone) were mostly prescribed during the study period. CONCLUSION: In this study, most steroids were indicated for respiratory disorders and prednisolone was found to be the most widely prescribed medication among systemic steroids.